2009
DOI: 10.1108/02602280910967620
|View full text |Cite
|
Sign up to set email alerts
|

Measurements in harsh RF propagation environments to support performance evaluation of wireless sensor networks

Abstract: We describe methods for evaluating the performance of wireless devices such as wireless sensors in harsh radio environments. We describe how measurements of real-world propagation environments can be used to support the evaluation process. We then present representative measurement data from high-multipath environments where sensor networks are likely to be deployed: a fixed-infrastructure, process-control environment, here an oil refinery, and a heavy industrial environment, here an automotive assembly plant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
5
0
5
Order By: Relevance
“…Em [13] foram descritas medições de propagação em ambientes industriais, visando avaliar fatores ambientais que influenciam na qualidade do canal, como a geometria do ambiente e as características dos objetos existentes no ambiente. O espalhamento de atraso eficaz para altas frequências (exemplo: 2,4 GHz) foi de 80 ns no pior caso.…”
Section: Perfil De Atraso De Potência E Largura De Banda De Coerênciaunclassified
“…Em [13] foram descritas medições de propagação em ambientes industriais, visando avaliar fatores ambientais que influenciam na qualidade do canal, como a geometria do ambiente e as características dos objetos existentes no ambiente. O espalhamento de atraso eficaz para altas frequências (exemplo: 2,4 GHz) foi de 80 ns no pior caso.…”
Section: Perfil De Atraso De Potência E Largura De Banda De Coerênciaunclassified
“…The latter was discussed in detail in [5] with respect to the use of single-frequency statistics to classify channels. The oil refinery was also discussed in [28] and [29] as part of overviews on the difficulties faced by public-safety practitioners and wireless sensor networks, respectively, in high-multipath environments. Here, we discuss how a combination of the metrics above can help to identify classes of propagation environments that may be important to the emergency response community.…”
Section: A Overviewmentioning
confidence: 99%
“…However, in harsh industrial environments, wireless communication systems are also subject to impulsive noise [8][9][10][11][12][13][14][15][16][17][18]. The major sources of impulse noise in industrial environments are motors, heavy machineries, ignition systems, inverters, voltage regulators, electric switch contacts, welding equipments, etc.…”
Section: Noise and Interference Noisementioning
confidence: 99%
“…Radio frequency (RF) measurement results of industrial WSNs are reported in [6,[12][13][14]. In http://jwcn.eurasipjournals.com/content/2012/1/297 [15], the path loss and the root mean square delay spread of the signal in industrial environment were investigated.…”
Section: Introductionmentioning
confidence: 99%